Increasing Women Representation in Entrepreneurial Activity-A Study of Mysuru City - Poovamma , K.N. (International Journal of Psychosocial Rehabilitation, 2020)
Abstract--- Growth of nation is only possible if the women of the nation are empowered. Independent decision making and financially free are the signs of empowerment which can be attained by becoming self-employed i.e., becoming an entrepreneur. Many dreams but only few dare to do so. The present study tries to understand the inbuilt factors that motivate a woman to become a successful woman. Researcher tries to identify the push and pull factors contributing towards increasing women representation in entrepreneurial activities. Descriptive research and non-probability based convenient sampling methods are adopted for the study covering the area of Mysuru city. It was ranked the various factors like to earn money and be independent as highest-ranking pull factor, family need support as push factor to challenging factors and health problem of husband as lowest rank of pull and push factor. It was identified that women could service through this mode to help the needy women society and empower them further.